2021
DOI: 10.1159/000516165
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Differences in Opioid Overdose Deaths between Scotland and England/Wales: Implications for European Opioid Policies

Abstract: <b><i>Backgrounds:</i></b> Between 2009 and 2018, the number of opioid-related deaths (ORDs) in Scotland showed a dramatic increase, whereas in England and Wales, a much lower increase in ORD was seen. This regional difference is remarkable, and the situation in Scotland is worrisome. Therefore, it is important to identify the drivers of ORD in Scotland. <b><i>Methods:</i></b> A systematic literature review according to PRISMA guidelines was conducted to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
(53 reference statements)
0
25
0
Order By: Relevance
“…A recent systematic review carried out by van Amsterdam et al [5] concluded that the increased opioids overdose deaths in Scotland compared to England and Wales can be explained by multiple factors, notable amongst which are concurrent use of benzodiazepines and gabapentinoids. These findings confirm data from North-American studies identifying concurrent benzodiazepine use as increasing risk of fatal overdose in opioid users.…”
Section: Generalizability Comparison To Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review carried out by van Amsterdam et al [5] concluded that the increased opioids overdose deaths in Scotland compared to England and Wales can be explained by multiple factors, notable amongst which are concurrent use of benzodiazepines and gabapentinoids. These findings confirm data from North-American studies identifying concurrent benzodiazepine use as increasing risk of fatal overdose in opioid users.…”
Section: Generalizability Comparison To Existing Literaturementioning
confidence: 99%
“…A recent study of fatal opioid overdose decedents in the UK is lacking [5]. We describe findings from a retrospective cross-sectional study using routine linked data to identify and describe characteristics of death (including substances involved and intent), demographic characteristics, residential mobility, and patterns of healthcare service usage of opioid overdose decedents over 3 years prior to death.…”
Section: Introductionmentioning
confidence: 99%
“…A Canadian study found that among people who injected drugs, participation in low-threshold OAT (also among those receiving Met) in primary care settings was significantly associated with improved survival [28]. In contrast, lower OAT coverage and efficacy in Scotland than England/Wales have been mooted as an explanation for the opioid crisis and deaths in Scotland [37].…”
Section: Discussionmentioning
confidence: 99%
“…Annual deaths from prescription opioids have quadrupled over the last couple of decades plus, more recently, heroin deaths quadrupling over the last decade, as well as a recent explosion in deaths involving fentanyl and analogues (mostly illicitly manufactured) [1]. Europe has a variable problem [2], with some countries such as Scot-land severely afflicted, and nearly 9,000 European citizens dying annually of opioid overdose (strangely higher in northern Europe) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%